The Anniversary That Continues. Willaschek, M. (2025). Kant. The Revolution of Thought. (V. Terletskyi, Trans.). Kyiv: Tempora. - Zabolotniy, Dmytro (Sententiae, 2025)
Review of Willaschek, M. (2025). Kant. The Revolution of Thought. (V. Terletskyi, Trans.). Kyiv: Tempora.